Высокодобротные резонаторные микроструктуры - Близнюк, И. Ю.; Бондаренко, И. Н. (ХНУРЕ, 2018)
Ananalysisoftheexistingtypes of microwave resonance structures has been carried out to identify the possibilities and prospects of their miniaturization while maintaining high Q values.
Keywords: Резонаторные микроструктуры